PENINGKATAN KESADARAN BAHAYA ROKOK UNTUK MENURUNKAN ANGKA MEROKOK PADA ANAK DI SEKOLAH DASAR NEGERI 32 ANDALAS KECAMATAN PADANG TIMUR KOTA PADANG - Melisa Yenti; Anggela Pradiva Putri; Hamidatul Yuni; Dela Desmita Sari; Hanifa Eka Putri; Shabrina Erika (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
The 2023 Indonesian Health Survey data shows that the 15-19 age group accounts for the highest percentage of smokers (56.5%), followed by the 10-14 age group (18.4%). This data indicates that children are among the groups with a significant likelihood of becoming a generation of smokers. Lack of understanding of children regarding the dangers of cigarettes, widespread exposure to cigarette advertisements in various media, easy access to cigarettes without age restrictions, and the influence of the social environment have a significant influence on children to smoke. Providing education on the dangers of cigarettes needs to be done from childhood to reduce the number of beginner smokers. This activity aims to increase students' knowledge and awareness of the dangers of cigarettes so that it can prevent and reduce the number of cigarettes in children. This activity occurred at SDN 32 Andalas, Padang City, targeting all 53 students in grades 5 and 6. The methods used were counseling, distribution of leaflets, and installation of posters about the dangers of cigarettes. After the activity was carried out, there was an increase in the average value of students' knowledge level, from 6.25 in the pre-test to 7.58 in the post-test, with a p-value of 0.001 (<0.005). So, it can be concluded that the education that was carried out successfully increased students' knowledge regarding the dangers of cigarettes. Thus, it is hoped that students will be aware of the dangers of cigarettes and will be motivated not to smoke. It is also extended to SDN 32 Andalas to continue educating students not to smoke, implementing a smoke-free area, and strictly supervising students who smoke.